Strengthening of Human Resources and Assistance for Sharia-Based Micro Enterprises - Muhammad Arif; Firdaus; Mufti Hasan Alfani (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The problem of Community Service Activities (PkM) is based on the wide-spread conditions of micro-businesses in Pekanbaru City, including in Air Dingin sub-district. However, many of these micro businesses are not followed by good business management, they face problems including low product sales, lack of variety in promotions, none of the business legality, business financial records that do not meet standards, and no halal certification. The solution prepared by the proposer is to provide guidance about sharia-based business governance, assistance in the management of business permits, assistance in creating business promotion concepts (digitized marketing), assistance in preparing financial reports and assistance with halal certification registration. It is hoped that this service can help improve the quality of human resources and the realization of sharia-based micro-enterprises as well as the implementation of Catur Dharma at Islamic University of Riau. The output of this PkM activity is in the form of publications in national mass media and publications in national scientific journals. This activity also will be carried out in the form of assistance to micro-entrepreneurs located in Air Dingin sub-district, Bukit Raya District, Pekanbaru City. Through this activity in the form of the assistance, it is hoped that there will be sustainable collaboration in various relevant fields between the Sharia Economics and Sharia Banking Study Program and micro businesses in Air Dingin sub-district, Pekanbaru. This community service activity regarding strengthening of human resources and assisting with sharia-based businesses is highly expected by micro businessmen because it can broaden their insight and feel like they are receiving training and assistance for their business